Feedlot lameness: industry perceptions, locomotion scoring, lameness morbidity, and association of locomotion score and diagnosis with case outcome in beef cattle in Great Plains feedlots - Terrell, Shane Patrick (Kansas State University, 2016)
In current literature, there is a limited amount of large scale data available demonstrating lameness morbidity in beef cattle feedlots, the subsequent outcomes of individuals exhibiting lameness, the morbidity and mortality of various lameness diagnoses, or the effect of locomotion score at the time of first morbidity and its effect on outcome. In addition, current perceptions of lameness by feedlot industry participants are not known and a reliable locomotion scoring system fit for use in a feedlot setting has not been developed. Consequently, the objectives of this research were three-fold. First, to obtain a baseline of the perception of lameness within the feedlot industry. Second, to develop a functional locomotion scoring system for use in feedlots and to test a training program implementing this locomotion scoring system for inter-rater reliability. Third, determine the association of lameness diagnosis and locomotion score at time of initial lameness diagnosis with case outcome in feedlot cattle and provide beef cattle feedlot lameness morbidity, mortality, and realizer incidence rates due to different lameness etiologies in a large scale, multisite study. One hundred forty-seven consulting nutritionists, veterinarians, and feedlot managers participated in the feedlot cattle lameness survey. The median response of estimated lameness incidence in the feedyard was 2%, with a mode of 1% and a mean of 3.8%. Participants indicated that footrot, injury, and toe abscesses were the most common causes of lameness. A locomotion scoring system was developed to clinically assess locomotion of beef cattle. The scoring system consisted of 4 categories: normal movement (0), slightly affected gait (1), obviously shortened stride or bobbing of head (2), and reluctance to move or apply weight to the limb while walking or standing (3). A total of 50 commercial feedlot employees and agricultural students were trained to use the scoring system in either English or Spanish. The scoring system was tested for inter-rater agreement and rater agreement against a cooperative standard based on consensus score by a team of individuals involved in the development of the scoring system, which included beef cattle veterinarians and welfare experts. Intra-class correlation coefficient (ICC) and Fleiss’s kappa were used to evaluate inter-rater agreement and rater agreement against the cooperative standard. Inter-rater agreement using ICC was 0.85 (95% CI; 0.75 to 0.93) while the mean kappa value was 0.52 (moderate agreement). Rater agreement with the cooperative standard resulted in mean kappa value of 0.64 (substantial agreement). A dynamic population longitudinal study with an initial study population of 245,494 head of feedlot cattle, with 524,780 animal arrivals and 527,220 animal departures recorded over the 12-month study was conducted over a year by trained personnel in six participating feedlots located in Kansas and Nebraska. Lameness morbidity incidence was 1.04 cases per 100 animal-years; lameness mortality was 0.397 cases per 100 animal-years. Cattle locomotion score (LMS; scale of 0 to 3 at time of initial diagnosis) were LMS1(22% of lameness cases), LMS2 (31%), and LMS3(22%). 24% of the lameness cases were not assigned a locomotion score (NS). Mortality risks were greatest for LMS3 (33.0%) and NS (31.3%), and were least for LMS1 (10.0%) with LMS2 (19.1%) being intermediate (P < 0.05).
Keywords: Beef; Bovine; Feedlot; Lameness; Welfare